Analisis Kalimat Imperatif dalam Video Tutorial Skincare Tasya Farasya di YouTube (LITERATUS, 2023)
In order to follow the procedures for utilizing good and appropriate skincare in the Tasya Farasya skincare lesson youtube video, this study intends to uncover the types of imperative sentences in the film. Sentences with imperatives are those that issue commands. Oral or written instructions may be given for this. According to the Great Dictionary of the Indonesian Language (KBBI), imperative sentences serve as directives or orders in general. An imperative statement directs or asks the listener to act in the speaker's preferred way. The research methodology utilized in this study is qualitative research, which aims to understand what the research subject is feeling by expressing it in language or words in a context using a scientific technique. The author of this study has chosen to use a qualitative method of research because the researcher's title is more focused on describing something, and the qualitative design is consistent with the researcher's title given that this study also aims to analyze the imperative sentences found in Tasya Farasya's YouTube videos. This study adopted a descriptive qualitative methodology.